Cancer and severe mental illness in low‐ and middle‐income countries: The challenges and outlook for the future. Issue 12 (27th August 2021) - Park, Sung Jin; Wai, Alisa; Pavithran, Keechilat; Kunheri, Beena; Valsraj, Koravangattu
Abstract: Objective: Patients with severe mental illness (SMI) face health inequalities that lead to under treatment of diseases such as cancer and result in increased mortality. There is literature addressing this issue for SMI patients in high‐income countries but few for those in low‐ and middle‐income countries. This review aims to draw attention to the health inequalities and the compounding factors faced by SMI patients in low‐ and middle‐income countries. The relevance of integration of psycho‐oncology in the care of SMI patients with cancer is integral to reduce disparities and address varied contributory factors. Methods: The literature review was conducted by searching through two databases which includes PubMed and Google Scholar. We searched for articles using keyword search terms: severe mental illness, SMI, schizophrenia, bipolar disorder, cancer, low‐ middle‐income countries, low‐ and middle‐income countries, psycho‐oncology, HPV vaccine, cancer incidence, cancer mortality, cancer control, cancer screening, cancer treatment and palliative care. Results: A total of 80 research articles were included in our literature review. We found that there was an increased requirement for adapting to the changing disease landscape in low‐ and middle‐income countries. An improvement on aspects such as vaccination, screening and prevention is necessary, and also efforts to change social stance towards SMI is crucial. Conclusion: There is an increase incidence of cancer in low‐ and middle‐income countries, and the number of patients with SMI in low‐ and middle‐income countries is also rising. This is due to social, psychological, economical and healthcare factors. Low‐ and middle‐income countries must consider improving these aspects in order to adapt to the changing landscape.